The Role of the Supply Chain Managaemnt in Accounting Information Systems in the Industrial Revolution 4.0 - Endraria Endraria (International Journal of Supply Chain Management, 2020)
Abstract- Utilization of Supply Chain Management (SCM) practice by businesses has a number of consequences for internal management information systems. The fourth industrial revolution will have a monumental impact on the global economy, so vast and multifaceted that it makes it hard to disentangle one particular effect from the next. Indeed, all the big macro variables one can think of GDP, investment, consumption, employment, trade, inflation and so on will be affected. This paper contributes to discussion concerning the desirability of improving external reporting and audit assurance by identifying and reporting internally generated qualitative SCM information that is critical to achievement of business objectives. The impact that the fourth industrial revolution will have on economic growth is an issue that divides economists. On one side, the techno pessimists argue that the critical contributions of the digital revolution have already been made and that their impact on productivity is almost over. In the opposite camp, techno-optimists claim that technology and innovation are at an inflection point and will soon unleash a surge in productivity and higher economic growth. Strategic management processes in place in almost all businesses already produce vital strategic information related to continuous analysis and monitoring of environmental issues including those relevant to SCM.